Pengaruh Lingkungan Kerja dan Burnout terhadap Motivasi serta Implikasinya pada Kinerja Pegawai BAPPEDA Jawa Barat - Maulana, Faizal Akbar; Suwandi, Yudi W. (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
When employees experience fatigue or boredom at work due to conditions that can't be predicteed in advance, this will disrupt the psychological condition known as burnout, and if it can't be control, it will affect work motivation. The work environment and burnout feel by employees affect work motivation, and if they can't be overcome, they will affect performance. The aim of this research is to determine the influence of the work environment and burnout on motivation and its implications for the performance of West Java BAPPEDA employees. Descriptive quantitative research method, research sample of 147 permanent employees (ASN) BAPPEDA West Java.  The research results found that simultaneously, the work environment and burnout had a significant effect on the motivation of West Java BAPEDDA employees. Meanwhile, partially motivated employees have a significant effect on the performance of West Java BAPEDDA employees.